2010
DOI: 10.1016/j.jss.2009.11.491
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with Histone Deacetylase Inhibitor Attenuates MAP Kinase Mediated Liver Injury in a Lethal Model of Septic Shock

Abstract: Background-Despite global efforts to improve the treatment of sepsis, it remains a leading cause of morbidity and mortality in intensive care units. We have previously shown that suberoylanilide hydroxamic acid (SAHA), a histone deacetylase inhibitor, markedly improves survival in a murine model of lipopolysaccharide (LPS)-induced shock. SAHA has antiinflammatory properties that have not been fully characterized. The liver plays an important role in the production of acute phase reactants involved in the infla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…This finding is in accordance with the literature, which shows that attenuating MAPK expression is protective because MAPK signaling pathways are associated with apoptotic cell death and inflammation. 22Y24 This also supports our previous work that showed that histone deacetylase inhibitors suberoylanilide hydroxamic acid 25 and VPA 26 significantly attenuate MAPK expression. Interestingly, PCR data revealed that MAP2K1 (MEK1 protein kinase), which lies upstream of MAPK, was upregulated in the HEX + VPA group.…”
Section: Discussionsupporting
confidence: 82%
“…This finding is in accordance with the literature, which shows that attenuating MAPK expression is protective because MAPK signaling pathways are associated with apoptotic cell death and inflammation. 22Y24 This also supports our previous work that showed that histone deacetylase inhibitors suberoylanilide hydroxamic acid 25 and VPA 26 significantly attenuate MAPK expression. Interestingly, PCR data revealed that MAP2K1 (MEK1 protein kinase), which lies upstream of MAPK, was upregulated in the HEX + VPA group.…”
Section: Discussionsupporting
confidence: 82%
“…The concentration of SAHA (1 lM) falls within the range of the peak serum concentration achieved in patients treated with effective oral anti-tumor doses of this compound (Kelly et al 2005). Moreover, the fact that SAHA was shown to induce changes in inflammatory markers in a mouse model of septic shock (Finkelstein et al 2010) suggest that SAHA may have secondary beneficial effects in PD besides normalizing CDK6 levels. On the other hand, NaB has been reported to reduce degeneration of dopaminergic neurons in a mutant alpha-synuclein drosophila transgenic model of familial PD (Kontopoulos et al 2006) and to rescue the rotenone-induced locomotor impairment and early mortality in flies (St Laurent et al 2013), suggesting a possible benefit in the early step of PD.…”
Section: Discussionmentioning
confidence: 70%
“…L IVER PLAYS AN important role in the production involved in the inflammatory cascade and is also one of the major organs that can become dysfunctional in septic shock. 1 Kupffer cells (KC) have an exquisite capacity for producing inflammatory cytokines 2 and the exaggerated pro-inflammatory cytokines induces liver injury. 3 On the contrary, methylprednisolone, an antiinflammatory agent, suppresses the pro-inflammatory cytokines and liver injury in rats induced by lipopolysaccharide (LPS), 4,5 and in mouse animal models of endotoxic shock, dexamethasone attenuates LPS-induced serum pro-inflammatory cytokines and improves survival ratio in the lethal mouse models.…”
Section: Introductionmentioning
confidence: 99%